Reputation: 23
I"m trying to prove ¬ (A ∧ B) → (A → ¬ B) with the Lean theorem prover. I've set it up like so.
example : ¬ (A ∧ B) → (A → ¬ B) :=
assume h1: ¬ (A ∧ B),
assume h2: A,
show ¬ B, from sorry
I've tried using and.left and and.right for h1 but these do not work when the conjunction is negated. I am unable to find any examples that prove implication like this starting from a negation. Any help would be much appreciated.
Upvotes: 1
Views: 1272
Reputation: 1129
¬ B
is defined to be B -> false
so you could start with
example (A B : Prop): ¬ (A ∧ B) → (A → ¬ B) :=
assume h1: ¬ (A ∧ B),
assume h2: A,
assume h3: B,
show false, from sorry
Upvotes: 2